Experimental and numerical investigations on coupled thruster and hull interactions for a benchmark ASD tug. (March 2022) - Yiew, Lucas J.; Taskar, Bhushan; Jin, Yuting; Zheng, Yingying; Liu, Daniel; Magee, Allan R.
Abstract: The propulsive performance of a benchmark azimuthing stern drive (ASD) tug is evaluated through a series of model-scale experiments and numerical simulations. Thruster–thruster and hull–thruster interactions are individually analysed by isolating each effect through a system of openwater, appended hull and free-running tests. Parametric studies are conducted for a range of advance ratios, thruster azimuth and hull drift angles. This study identifies the regimes where thruster–thruster and hull–thruster effects are significant. Results from this study are used to develop higher fidelity propulsion models and a digital twin of a tug, which can simulate the hydrodynamic behaviour and response of the vessel in real-time.